Supplementation of sperm cooling medium with Eurycoma longifolia extract enhances native Thai chicken sperm quality and fertility potential - Koedkanmark, Thirawat; Ratchamak, Ruthaiporn; Authaida, Supakorn; Boonkum, Wuttigrai; Semaming, Yoswaris; Chankitisakul, Vibuntita (Frontiers in Veterinary Science, 2024)
Cooled semen storage methods result in oxidative stress generated by an imbalance between oxidation rates, specifically reactive oxygen species production, and sperm cell antioxidants, leading to degradation of semen quality. We aimed to investigate the impact of adding Eurycoma longifolia (EL) extract as an antioxidant supplement in semen storage medium (IGGKPh semen extender) on semen quality and fertility potential. EL extract at concentrations of 5, 10, 15, and 20 mg/mL was assessed for its antioxidant capacity in IGGKPh semen extender. Our findings revealed that the total phenolic content in the EL extract did not vary significantly across the various concentrations and temperatures tested. However, incubation at 5°C was found to be the most effective temperature for increasing the EL extract antioxidant capacity as assessed via the 2,2-diphenyl-1-picrylhydrazyl inhibition assay in a dose-dependent manner. Supplementation of the IGGKPh semen extender with 15 mg/mL EL extract was found to enhance semen quality during cold storage for up to 48 h (p < 0.05), as evidenced by decreased malondialdehyde levels in cooled semen (p < 0.05). However, antioxidant enzyme activities showed no significant differences among the various experimental groups (p > 0.05). The fertility test showed that the 15 mg/mL EL extract group stored for 24 h had a higher percentage than the control group (p < 0.05). However, there was no significant difference in percentage between the two groups at 48 h of storage (p > 0.05). The hatchability showed no significant difference in both 24 and 48-h storage periods (p > 0.05). Our results indicated that supplementing the IGGKPh semen extender with 15 mg/mL EL extract may positively influence semen quality during storage, suggesting potential applications for enhancing semen quality.